A Systematic Review of the Symptom Distress Scale in Advanced Cancer Studies. Issue 4 (July 2016) - Stapleton, Stephen J.; Holden, Janean; Epstein, Joel; Wilkie, Diana J.
Abstract : Background: The 13-item Symptom Distress Scale (SDS) is a widely used symptom measurement tool, yet a systematic review summarizing the symptom knowledge generated from its use in patients with advanced cancer is nonexistent. Objectives: This was a systematic review of the research literature in which investigators utilized the SDS as the measure of symptoms in patients with advanced cancer. Methods: We searched PubMed, CINAHL, EMBASE, and Web of Science for primary research studies published between 1978 and 2013 that utilized the SDS as the measurement tool in patients with advanced cancer. Nine hundred eighteen documents were found. Applying inclusion/exclusion criteria, 21 articles and 2 dissertations were included. Results: The majority of investigators utilized descriptive, cross-sectional research designs conducted with convenience samples. Inconsistent reporting of SDS total scores, individual item scores, age ranges and means, gender distributions, cancer types, cancer stages, and psychometric properties made comparisons difficult. Available mean SDS scores ranged from 17.6 to 38.8. Reports of internal consistency ranged from 0.67 to 0.88. Weighted means indicated fatigue to be the most prevalent and distressing symptom. Appetite ranked higher than pain intensity and pain frequency. Conclusions: The SDS captures the patient's symptom experience in a manner that informs the researcher or clinician about the severity of the respondents' reported symptom distress. Implications for Practice: The SDS is widely used in a variety of cancer diagnoses. The SDS is a tool clinicians can use to assess 11 symptoms experienced by patients with advanced cancer.